Jack and the beanstalk - Daynes, Katie (London : Usborne Publishing Ltd, 2006)
When Jack sells the family cow for five dried beans, his mother is furious. But overnight the beans sprout into a giant beanstalk. Join Jack as he climbs the stalk... and discovers a dangerous world about the clouds.
Shelving Location Readers Section. Fiction Book Section
Keywords: Children's fiction